THE TACTIC COMPONENT OF MODERN STATES’ FOREIGN POLICIES IN THE SYSTEM OF GLOBAL GOVERNANCE - Запорожченко, Р. О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
The present paper deals with the issue of the role and place of a modern state in the system of global governance. The theoretical and methodological conceptions of global governance and their implementation in modern research have been analyzed. The specificities of the tactic component of the states’ foreign policies and the indicators (parameters) for their classification have been determined. The typology of modern states’ tactics with the account for their structural and functional as well as value and normative parameters has been worked out.